Preening Behavior of Adult Gyrfalcons Tagged with Backpack Transmitters - Booms, Travis L.; Schempf, Philip F.; Fuller, Mark R. (Journal of Raptor Research, 2011)
Radio transmitters provide data that enhance understanding of raptor biology (Walls and Kenward 2007) and are now used to answer a multitude of research questions (Meyburg and Fuller 2007). However, transmitters affect the birds that carry them (Barron et al. 2010), and it is important to document and evaluate such effects (Casper 2009). For example, decreased survival has been documented in Prairie Falcons (Falco mexicanus; Steenhof et al. 2006), Northern Goshawks (Accipiter gentilis; Reynolds et al. 2004), and Spotted Owls (Strix occidentalis; Paton et al. 1991) tagged with radio transmitters. However, no such effects were reported for Peregrine Falcons (Falco peregrinus; Fuller et al. 1998, McGrady et al. 2002) and a number of other species (Kenward 2001). White and Garrott (1990) noted that in general, animals tagged with radio transmitters often altered their behaviors for 1–14 d after release during an adjustment period that included increased preening and grooming frequencies. Although more than 90 Gyrfalcons (Falco rusticolus) have been tagged with radio transmitters (e.g., Burnham 2007, McIntyre et al. 2009, T. Booms unpubl. data), the effects of transmitters on this species are not well documented. Anecdotal information suggests some Gyrfalcons might be negatively affected by radio-tagging (Booms et al. 2008). As part of a study investigating Gyrfalcon breeding biology, we conducted opportunistic, focused observations on two radio-tagged adult female Gyrfalcons and their unmarked mates. We here describe and quantify preening behavior of Gyrfalcons shortly after radio-tagging.